PENDIDIKAN KESEHATAN METODE SIMULATION GAME MENINGKATKAN PERILAKU PENDERITA DIABETES MELLITUS DALAM MELAKUKAN PERAWATAN KAKI DI POSYANDU LANSIA SIMOANGIN-ANGIN SIDOARJO - Siska Dwi Purwaningtyas; Kusnanto Kusnanto; Retno Indarwati (Universitas Airlangga, 2019)
Introduction: The Diabetes patient’s have risk of gangrene 5 times greater than that effect of amputation and death. Prevalence of diabetic foot most happens in under 60 years old about 80% than > 60 years old. Health education on a diabetes foot care can prevent diabetic foot, beside blood glucose regulation. The objective of this study was to analyze the influence of simulation game of diabetic foot care toward behavior the patient with Diabetes mellitus.Method: The research used pre experimental pre-post test design with purposive sampling. The population was patients Diabetes mellitus in Posyandu Lansia Simoangin-angin. Total sample was 13 respondents, taken according to inclusion criteria. The independent variable was health education using simulation game method about diabetic foot care and the dependent variable’s were knowledge, attitude and action. Data were collected by using questioners then analyzed using wilcoxon signed ranks test, with level of significance p≤0.05.Result: The results showed significant changes in knowledge, attitude and action of diabetic foot care (p=0.002 for knowledge, p=0.034 for attitude, and p=0.004 for action) which means that there were influences of health education by simulation game of diabetic foot care on knowledge, attitude and action the patients with Diabetes mellitus in middle age at Posyandu Lansia Simoangin-angin.Discussion: It can be concluded that health education given by simulation game has influenced on knowledge, attitude and action of patients with Diabetes mellitus. The next research are expected to apply health education by simulation game in another cases.